Pengaruh Interaksi Sosial dan Kebersihan Hotel Terhadap Niat Pemesanan Hotel Melalui Risiko Kesehatan Pada Hotel Mercure, Jakarta - Marie, Andhalia Liza; Sulistyo, Tri Djoko; Ratnaningtyas, Heny (Jurnal Ilmiah Pariwisata; Vol 26 No 2 (2021): Jurnal Ilmiah PariwisataDO - 10.30647/jip.v26i2.1475, 2021)
This research is a quantitative research using path analysis method which distributes google form questionnaires to 100 customers of Hotel Mercure Jakarta. The data is processed using SmartPLS. The results showed that the interaction of social influence was significant on hotel booking intentions through health risks. Meanwhile,hotel cleanliness has no significant effect on hotel booking intentions through health risks. Then social interaction has a significant effect on hotel booking intentions. Furthermore, hotel cleanliness has no significant effect on hotel booking intentions. Health risk has a significant effect on hotel booking intentions. Hotel guests expect a low level of social interaction from check in to check out, which can pose a health risk and intend to make hotel reservations. Hotel cleanliness through health risks cannot increase hotel booking intentions. Hotel guests expect the hotel to make technological innovations that increase guest intention to make room reservations. Hotel cleanliness is not the main expectation of hotel guests, guests expect a low level of social interaction during their stay at the hotel. Keywords :  Social Interaction , Hotel Cleanliness , Hotel Booking Intention , Health Risk